1968
DOI: 10.1007/bf02667103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Arsenic in Marine Oils by Neutron Activation. Evidence of Arseno Organic Compounds

Abstract: The arsenic content of phospholipid fractions Ehtating Eluating separated from eodliver oil (Gadus morrhua) and Fraction agent volume herring oil (Clupea harengus) was analyzed by 1 A a Chloroform 210 7 O 65 % Methanol in chloroform 240 ganie compounds. Two such compounds were 8 H 90%Metl~anolinehloroform 270 evident in herring oil. a See Fig. i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

1970
1970
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 5 publications
1
36
0
2
Order By: Relevance
“…Lipophilic As compounds in marine organisms were first investigated by Lunde (Lunde 1968), although their actual molecular structures remained unknown for a long time (Morita and Shibata 1988). The first identified AsLipid was dipalmitoylglycerophospho-2-hydroxypropyl-5-deoxy-5-(dimethylarsinoyl)-beta-ribofuranoside in the brown alga, Unidaria pinnatifida (Morita and Shibata 1988).…”
Section: Sources and Distribution Of Organic As Species In Marine mentioning
confidence: 99%
“…Lipophilic As compounds in marine organisms were first investigated by Lunde (Lunde 1968), although their actual molecular structures remained unknown for a long time (Morita and Shibata 1988). The first identified AsLipid was dipalmitoylglycerophospho-2-hydroxypropyl-5-deoxy-5-(dimethylarsinoyl)-beta-ribofuranoside in the brown alga, Unidaria pinnatifida (Morita and Shibata 1988).…”
Section: Sources and Distribution Of Organic As Species In Marine mentioning
confidence: 99%
“…Kolakowska et al (21) reported 6.6 pg/g arsenic in cod liver and its oil. Lunde (22) reported 3.9 pg/g arsenic in the lipid extracts of cod liver and herring. The mercury concentration in different brands of fish oil studied by Foran et al (8) ranged from 6 to 12 pg/liter.…”
Section: )mentioning
confidence: 99%
“…Lunde in 1968 was the first to report that fish contained appreciable levels of lipid-soluble arsenic [8]. Benson and co-workers, however, were the first to investigate its formation in algae using a biochemical approach beginning with radiolabeled arsenate [9,10].…”
Section: How Does It Get There?mentioning
confidence: 99%